2001
DOI: 10.1002/1521-4095(200109)13:17<1317::aid-adma1317>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure Determination of Spherical MCM-41 Particles

Abstract: Experimental observations from (sub‐)micrometer spheres of silica are compared with the results from conventional MCM‐41 material. SEM images give proof of a spherical morphology (see Figure), which is also confirmed by TEM. XRD patterns confirm that on a local scale the pores are hexagonally packed whilst on a larger scale, the pore ordering is disturbed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 6 publications
3
67
0
1
Order By: Relevance
“…Figure 1 shows SEM micrographs of the catalysts and the support. As observed, MCM-41 appears to have a soft surface with some agglomerates of curved rods similar to the ones reported by other authors [44]. Otherwise, the catalysts show a more rugged and intricate morphology.…”
Section: Resultssupporting
confidence: 88%
“…Figure 1 shows SEM micrographs of the catalysts and the support. As observed, MCM-41 appears to have a soft surface with some agglomerates of curved rods similar to the ones reported by other authors [44]. Otherwise, the catalysts show a more rugged and intricate morphology.…”
Section: Resultssupporting
confidence: 88%
“…It can be used as effective materials in various cementitious system for improving the strength, flexibility, durability, workability, etc. Various synthetic strategies have been reported to prepare silica nanoparticles, such as the modified Stöber method (Grün et al 1999;Pauwels et al 2001;Liu et al 2003;Zhang et al 2004;Lebedev et al 2004;Tan et al 2004;Shimura et al 2005;Tan et al 2005), combustion techniques (Hong et al 2009), chemical vapor deposition (Awaji et al 1997), aerosol spray (Rao et al 2002;Bore et al 2003;Miller et al 2005),and emulsion (Oh et al 2005) method. Various types of morphology such as hexagonal, cubic, lamellar, and wormhole like mesostructures have been synthesized using these methods.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, solution synthesis of MSNs is carried out under basic and high dilution conditions in an alcohol-water mixture following the so-called modified Stöber method ( Figure 5.14) [151]. The most widely used alcohols are methanol, ethanol, n-propanol, or n-butanol, while ammonia is used as catalyst for colloidal growth [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156]. Under basic conditions, part of the silanol groups is deprotonated forming Si-O − species and, therefore, cationic surfactants are used to match the negatively charged silica surface.…”
Section: Modified Stöber Methodsmentioning
confidence: 99%
“…It has been widely reported that the particle sizes can be tuned by controlling synthetic parameters, such as pH, reaction time and temperature [147][148][149][150][151][152][153][154][155][156][157][158][159], and by adding certain compounds such as organics and organosilanes [160][161][162]. These parameters are greatly associated with the hydrolysis and condensation of the silica sources (e.g., TEOS).…”
Section: Modified Stöber Methodsmentioning
confidence: 99%